2017
DOI: 10.1021/acs.biomac.7b00568
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Electroconductive Hyaluronic Acid Hydrogels Incorporated with Carbon Nanotubes and Polypyrrole by Catechol-Mediated Dispersion Enhance Neurogenesis of Human Neural Stem Cells

Abstract: Electrically conductive hyaluronic acid (HA) hydrogels incorporated with single-walled carbon nanotubes (CNTs) and/or polypyrrole (PPy) were developed to promote differentiation of human neural stem/progenitor cells (hNSPCs). The CNT and PPy nanocomposites, which do not easily disperse in aqueous phases, dispersed well and were efficiently incorporated into catechol-functionalized HA (HA-CA) hydrogels by the oxidative catechol chemistry used for hydrogel cross-linking. The prepared electroconductive HA hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 75 publications
0
129
0
Order By: Relevance
“…First, HAC conjugates were synthesized via a chemical reaction using 1‐ethyl‐3‐(3‐(dimethylamino)propyl)‐carbodiimide hydrochloride (EDC) and N ‐hydroxysuccinimide (NHS) as carboxyl activating agents (Figure S1, Supporting Information). The successful modification of catechol was confirmed by 1 H nuclear magnetic resonance ( 1 H NMR), which demonstrated that the degree of catechol was ≈34.2% (Figure S2, Supporting Information). Meanwhile, the ultraviolet–visible (UV–vis) spectrum of HAC showed a new peak at 280 nm (Figure S3, Supporting Information), which is attributed to the absorption of benzene ring in dopamine .…”
mentioning
confidence: 94%
“…First, HAC conjugates were synthesized via a chemical reaction using 1‐ethyl‐3‐(3‐(dimethylamino)propyl)‐carbodiimide hydrochloride (EDC) and N ‐hydroxysuccinimide (NHS) as carboxyl activating agents (Figure S1, Supporting Information). The successful modification of catechol was confirmed by 1 H nuclear magnetic resonance ( 1 H NMR), which demonstrated that the degree of catechol was ≈34.2% (Figure S2, Supporting Information). Meanwhile, the ultraviolet–visible (UV–vis) spectrum of HAC showed a new peak at 280 nm (Figure S3, Supporting Information), which is attributed to the absorption of benzene ring in dopamine .…”
mentioning
confidence: 94%
“…Then we attached EBs in the new culture dish coated with Matrigel (BD Biosciences) with neural induction medium comprised of DMEM/F12 medium (11320033, Invitrogen), 1× N2 supplement (17502048, Invitrogen), 1× nonessential amino acids (11140050, Invitrogen) for 6 days. When neural rosette formation appeared in the center of the EBs, NPCs were collected for analysis [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion of electrospun fibers synthesized from collagen reduced stem cell survival and differentiation, while electrospun fibers of poly(ε-caprolactone-co-D,L-lactide) maintained stem cell survival and differentiation similar to HAMC alone [89]. Electroconductive HA composites have also been developed by incorporating carbon nanotube or polypyrrole into HA-based hydrogels [131]. Greater neuronal differentiation of human fetal neural stem cells and human induced pluripotent stem cell-derived neural progenitor cells in 3D culture was seen in these composite hydrogels compared to hydrogels alone [131].…”
Section: Composite Materials Systemsmentioning
confidence: 99%
“…Electroconductive HA composites have also been developed by incorporating carbon nanotube or polypyrrole into HA-based hydrogels [131]. Greater neuronal differentiation of human fetal neural stem cells and human induced pluripotent stem cell-derived neural progenitor cells in 3D culture was seen in these composite hydrogels compared to hydrogels alone [131].…”
Section: Composite Materials Systemsmentioning
confidence: 99%